Pemberdayaan Komunitas Teater Tradisi Melalui Karya Virtual Untuk Meningkatkan Kemampuan Information and Technology (IT) - Heny Purnomo; Tri Rusia Ningsih; Ratna Mestikasari Putri (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2023)
After the closure of the THR Surabaya complex (2019), the Irama Budaya ludruk community is now in a worrying situation of "stagnation". Until now, there is still no "vehicle" that is willing to accommodate this community to hold its performances again. Meanwhile, folk traditional theater performances (ludruk) which are held in person are now increasingly difficult to do and rarely found, in fact the growth and development of electronic social media (social media) has provided space for traditional theater to organize performances. In its development, live performances require a lot of money and take longer, this can make the audience feel bored, especially the younger generation. On the other hand, a lot of art is commodified through social media broadcasts which almost never leave any free time. The presence of electronic social media has created a new entertainment industry with artistic settings (scenography) supported by technological sophistication, whereas traditional theater performances are considered outdated, and often depend on supporting communities which are starting to decline. This social phenomenon has an impact on the behavior of today's audiences who prefer electronic media, especially YouTube, so that the traditional theater community needs to be "empowered" through virtual works to improve Information and Technology (IT) capabilities. Empowering the traditional theater community aims to put into practice starting from the process of preparing scenography equipment to editing various elements and elements of the artistic layout of virtual work performances. The method for empowering the traditional theater community is carried out through socialization (mentoring, training and production) and direct practice from resource persons. Through this empowerment, it is hoped that it can improve the IT capabilities of the traditional theater community in facing forms of audience transformation, and can utilize "electronic social media" as a new platform for presenting artistic performances through virtual works.